Biomimetic nanovaccines for COVID-19 - Singh, Bijay (Applied Science and Technology Annals, 2020)
The outbreak of Coronavirus Disease 2019 (COVID-19) has posed a serious threat to global public health, calling for the development of safe and effective prophylactics and therapeutics against infection of its causative agent, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Currently, there is no approved vaccines or medications exist to prevent infection by SARS-CoV-2. In this emergency, more than 100 vaccines formulated using conventional approaches are being explored against SARS-CoV-2 across the world. The vaccines formulated using nanotechnology are also on the race of clinical trials. The aim of this article is to provide an insight into the ways of vaccine production by conventional and nanotechnology platforms and expand the understanding on the possibilities and limitations of these approaches for vaccine developments.